PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BERDAMPAK KEPUASAN KONSUMEN (STUDI PADA SUPER SWALAYAN SAMPANGAN SEMARANG) (Students' Journal of Economic and Management, 2014)
The study titled Effects of Product Quality and Price Satisf action Impact Of Consumer Purchase Decision Self Sampangan Semarang Super Marketsis a study to determine and analyzewhether the variable product quality, price, and purchase decisions given by the Super Market Self Sampangan partially Semaranghas an influence onsatisfacti on consumers, this study took the title"THE EFFECT OF PRODUCTQUALITYANDPRICE ONPURCHASE DECISIONIMPACTOF CUSTOMER SATISFACTION". The samples usedin this study were100 respondents. The sampling techniqueused in the form of accidental sampling method or by selecting respon dentsin a  ccordance with the terms become a  resondenand by chance mettha thaves hoppedat  least 4 times and age less than 20 years. Data collected were tested be forehand using validity and reliability in order to obtain valid and reliable results that can be used in subse quent testing. Subsequent analys is the authors use regressi on testing to explain the relationship between the independent and dependent variables. The resultis a quality product(X1), price(X2), the purchase decision(Y) and a significant positive effecton customer satisfaction(Z). From the results of the regressi one quations that prices have thegreatest influenceand product qualityhas theleast influence. Resultsoftest of determination obtained variable product quality, price, purchase decisi on sare relatively large in explaining consumer satisfaction. This study has limitations that the variables used only in the variable product quality, price, purchase decision, while there are many other factors that can in fluencea consumer'ss at is faction. In addition, this study only examined on consumers who are visiting and shopping at the SuperSelf Sampangan Semarang. Therefore, furtherre searchis  recommended to consider other   not been found in this study and wider sampling Keywords: Variable Productquality, Price, Purchase Decision, Customer Satisfaction